Risk perception and vulnerability of value: a study in the context of commercial property sector - Bhattacharya-Mis, Namrata; Lamond, Jessica (International Journal of Strategic Property Management, 2016)
The research was developed linking the impact of flood risk on utility, desirability and marketability related to vulnerability of commercial property value. Likert style questionnaire survey was conducted to obtain data from flood affected and un-affected respondents across different designated flood risk zones on key business and perception variables among two groups of business property holders in England. The responses were analysed through a spatial vulnerability model to illustrate the distribution of the vulnerability of value of properties among flood plain business holders on a GIS platform. Majority of respondents perceived that utility of properties may be hampered by flooding and subsequently have an impact on value for property at risk. Those with flood experience gave greater weight to their specific business needs such as the prime location and expected income level than those without flood experience. The implication of the study lies in understanding that flood risk perceptions can shape actions of people at risk towards future increase in resilience having strategic impact on value of property saleability in the future.